The Nucleation, Formation and Propagation of Chernov-Lüders Bands in Welds Having Structure and Phase Inhomogeneity - Danilov V. I. Vladimir Ivanovich; Orlova D. V. Dina Vladimirovna; Gorbatenko V. Vladimir; Smirnov A. Aleksandr; Ozhiganov Ye. Yevgeny; Danilova L. Lidiya (2016, 2016)
Title screen